Bilibid weeks an account of prison theater - Abad, Ricardo G. (Perspective in the Arts and Humanities ASIA (formerly Asian Perspectives in the Arts and Humanities), 2019)
For three years, the training company RolePlayers, Inc., worked with young male inmates at the Special Classes for Children in Conflict with the Law (SC-CCIL), a unit of the New Bilibid Priso, in two theater productions that were shown to the prison community and the external public. The first production, staged in 2016, was a devised piece called Tumbang Preso (Knock down the Prisoner); the second production, mounted in 2018, was the Pyramus-Tisbe scene from William Shakespeare's A Midsummer Night's Dream, in Filipino translation. The production's immediate impact, however, lies beyond the plays. For the young inmates, prison theater served as an opportunity to learn new skills, gain new perspectives, receive emotional support, and increase their chances of getting released. This paper documents the prison-theater project, the challenges the organizers faced, the lessons they have learned, and the paths that can be taken to sustain prison theater.